Nutrient-Rich Organic Soil Management Patterns in Light of Climate Change Policy - Ieva Līcīte; Dina Popluga; Pēteris Rivža; Andis Lazdiņš; Raitis Meļņiks (Civil Engineering Journal, 2022)
Nutrient-rich organic soil management in agriculture is among the critical sources of greenhouse gas (GHG) emissions globally and at the European level, where the most significant effects are observed in Northern, Eastern, and Central Europe. Growing climate change mitigation targets urge the need to assess and analyze current organic soil management patterns and policy planning and look for appropriate future management strategies. The objectives of this research were to assess the nutrient-rich organic soil management patterns in Latvia during the last decade and to conclude whether organic soil management in agriculture has been climate change mitigation targeted and driven by agriculture support policy. We analyzed the complex, two state-level databases based organic soil data set by using the multidimensional approach of the research methods, including graphical, spatial, correlation, factor, and cluster analysis. Our results revealed the lack of purposeful organic soil management planning in light of the climate change policy in Latvia during the research period and the inexpediency of the agriculture support policy in this regard. The research introduced an innovative methodological approach for the analysis of organic soil management patterns and policy impacts, as well as opened the necessity for a revision of the nutrient-rich organic soil management perspective in light of climate change mitigation targets. Doi: 10.28991/CEJ-2022-08-10-017 Full Text: PDF